Pesantren dan Pergeseran Paradigma Epistemologi: Dari Humanisme Menuju Era Post-Humanisme - Anam, Ahmad Muzakkil; Ade Agustinova, Danang; Alwiyah, Noor; Haqqi Firmansyah, Nashrul (Santri: Journal of Pesantren and Fiqh Sosial, 2025)
This study explores the paradigm shift from humanism to post-humanism within the landscape of contemporary knowledge and its implications for the epistemology of pesantren education. Humanism, which places humans at the center of all things, has come under intense critique in the era of digital technology and artificial intelligence, giving rise to post-humanist perspectives that emphasize decentralized agency and the interconnectedness of humans, machines, and the environment. Pesantren, as traditional Islamic educational institutions, is grounded in a distinctive epistemology that integrates revelation, reason, and spiritual experience. This qualitative research employs a literature review and discourse analysis method to examine the epistemological constructions of humanism, post-humanism, and pesantren. The findings indicate that pesantren can occupy a synthetic position between these two contrasting paradigms—retaining their spiritual heritage and scholarly authority through sanad—while simultaneously transforming into educational institutions that are both relevant and adaptive in the post-humanist era. This critical approach positions pesantren as epistemic entities capable of fostering a creative dialogue between tradition and modernity, inspiring new ways of thinking and learning that bridge the gap between transcendental values and the realities of the digital age.